2017
DOI: 10.1186/s12917-017-1215-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical use of 5% acyclovir cream for the treatment of occult and verrucous equine sarcoids: a double-blinded placebo-controlled study

Abstract: Background: Previous studies mention the use of topical acyclovir for the treatment of equine sarcoids. Success rates vary and since the bovine papillomavirus (BPV) lacks the presence of a kinase necessary to activate acyclovir, there is no proof of its activity against equine sarcoids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
0
15
0
2
Order By: Relevance
“…Topical therapies generally seem particularly feasible as they are noninvasive and applicable, even on treatment sites that are difficult to access. However, the results regarding the efficacy of the acyclovir cream often used for mild-type ES treatment are contradictory [16,17] and imiquimod may temporarily cause severe local side effects [18]. In addition, although a variety of other topical treatment options exists, mainly anecdotal evidence of their success is reported [1,15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Topical therapies generally seem particularly feasible as they are noninvasive and applicable, even on treatment sites that are difficult to access. However, the results regarding the efficacy of the acyclovir cream often used for mild-type ES treatment are contradictory [16,17] and imiquimod may temporarily cause severe local side effects [18]. In addition, although a variety of other topical treatment options exists, mainly anecdotal evidence of their success is reported [1,15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, no negative control group was included in the study. Two previous studies showed tumour size reductions or resolution in untreated control groups of 14% 25 and 16% 26 …”
Section: Discussionmentioning
confidence: 93%
“…Two previous studies showed tumour size reductions or resolution in untreated control groups of 14% 25 and 16%. 26 . In another study, spontaneous remission was observed in ≤62% of horses during an observation period of five to seven years.…”
Section: Discussionmentioning
confidence: 99%
“…• Topical acyclovir: topical 5% acyclovir cream has been used to treat sarcoids with some benefits reported in one study [77]. A subsequent retrospective case-series and a double-blinded placebo-controlled trial resulted in no advantages from this agent compared to other treatments or placebo [70,78]. The cream is used without prescription for human herpes virus infection and this may be attractive for owners that desire to treat horses without looking for veterinary advice with deleterious effects [3].…”
Section: Chemotherapymentioning
confidence: 99%